Structural studies of tetrachloride liquids. III - Molecular structure of CCl4, SiCl4, TiCl4, GeCl4 and SnCl4. - Granada, J. R. (1979)
Fil: Granada, J. R. Comisión Nacional de Energía Atómica; Argentina